Understanding and utilising social media analytics tools - Kamarulzaman, Rabiatul Adawiyah; Lehat, Mohd Lezam; Kamarudin, Nurfaizah; Baharin, Siti Hajar (Universiti Teknologi MARA, Johor, 2025)
Social media has become an integral part of communication, marketing, and education. With millions of users engaging daily, understand how content performs is crucial for businesses, educators, and influencers. Social media analytics tools help in measuring performance, understanding audience behaviour, and optimising content strategies. This essay explores the key analytics tools available for three major social media platforms: Facebook, Instagram, and TikTok, highlighting their importance in decision-making and engagement optimization.